2010
DOI: 10.1103/physrevb.81.064509
|View full text |Cite
|
Sign up to set email alerts
|

Bulk electronic structure of optimally dopedBa(Fe1xCox)2

Abstract: We report high-resolution, bulk Compton scattering measurements unveiling the Fermi surface of an optimally doped iron-arsenide superconductor, Ba͑Fe 0.93 Co 0.07 ͒ 2 As 2 . Our measurements are in agreement with first-principles calculations of the electronic structure, revealing both the X-centered electron pockets and the ⌫-centered hole pockets. Moreover, our data are consistent with the strong three dimensionality of one of these sheets that has been predicted by electronic structure calculations at the l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
18
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 34 publications
(22 reference statements)
8
18
0
Order By: Relevance
“…41, 140 which shows a peak at Q AF , which is at the corner M point of the primitive tetragonal Brillouin zone in the bottom panel of Fig. 14 above. A similar enhancement of χ(Q) at the M point was found for LaFeAsO in more refined calculations by Monni et al 264 Utfeld et al have calculated that the noninteracting χ(Q) for optimally doped Ba(Fe 0.93 Co 0.07 ) 2 As 2 still has a pronounced peak near the nesting wave vector, in spite of significant 3D dispersion of one of the hole Fermi pockets, 158 and Yaresko et al also found peaks in the noninteracting χ(Q) for both doped and undoped LaFeAsO 1−x F x and (Ba 1−x K x )Fe 2 As 2 , 266 thus supporting the s ± supercon-ducting pairing model (see below). An early unbiased numerical investigation of a two orbital model gave robust evidence for the stability of the stripe state in the undoped iron arsenides.…”
Section: -Type Compoundssupporting
confidence: 68%
See 1 more Smart Citation
“…41, 140 which shows a peak at Q AF , which is at the corner M point of the primitive tetragonal Brillouin zone in the bottom panel of Fig. 14 above. A similar enhancement of χ(Q) at the M point was found for LaFeAsO in more refined calculations by Monni et al 264 Utfeld et al have calculated that the noninteracting χ(Q) for optimally doped Ba(Fe 0.93 Co 0.07 ) 2 As 2 still has a pronounced peak near the nesting wave vector, in spite of significant 3D dispersion of one of the hole Fermi pockets, 158 and Yaresko et al also found peaks in the noninteracting χ(Q) for both doped and undoped LaFeAsO 1−x F x and (Ba 1−x K x )Fe 2 As 2 , 266 thus supporting the s ± supercon-ducting pairing model (see below). An early unbiased numerical investigation of a two orbital model gave robust evidence for the stability of the stripe state in the undoped iron arsenides.…”
Section: -Type Compoundssupporting
confidence: 68%
“…158 These bulk data indicate substantial dispersion of one or both hole Fermi surfaces along k z that are in agreement with LDA band calculations in the virtual crystal approximation with the optimized As position, with the best agreement obtained after rigidly shifting the electron and hole bands in energy in opposite directions. 158 …”
supporting
confidence: 77%
“…In this concern, it is worth mentioning that also the relative weight of the two terms in the conductance (let's say, w 1 and (1 − w 1 )) is the same irrespective of the direction of the current. This seems to indicate that all the FS sheets have a similar degree of three-dimensionality, as also shown by ARPES [61] and x-ray Compton scattering [62]. Thick lines in figure 9(c) represent the two-gap 2D BTK fit of the curves, while thin lines indicate the single-gap 2D BTK fit.…”
Section: Ba(fe1−xcox)2as2supporting
confidence: 68%
“…This careful comparison further showed that a rigid upward shift of the Fermi energy by 11mRy ($0.15 eV) was necessary to bring the theoretical calculation for LaRu 2 Si 2 into agreement with experiment. This kind of shift (albeit for individual bands, rather than a global shift) was found to be necessary recently in Fermi surface measurements in the Fe-pnictide superconductors on the basis of quantum oscillations 70 and Compton scattering, 71 and has also been found to be necessary to accurately reproduce Fermi surfaces in other materials. 72,73 As Monge et al pointed out, however, if such shifts are necessary even without the complexities introduced by f electrons, it does call into question the assertion, based on such LDA calculations and dHvA data, 69,74 that the f electrons are itinerant in the heavy fermion state.…”
Section: Ceru 2 Si 2 and Laru 2 Simentioning
confidence: 99%